The role of self-compassion in diabetes management: A rapid review - Sandham, Courtney; Deacon, Elmari (Frontiers in Psychology, 2023)
Aim: This study aimed to assemble and critically reflect on previously acquired insights from investigations that have already been conducted into the role of self-compassion in diabetes management. Methods: This study implemented a rapid review approach to assess the pre-existing knowledge in a time-sensitive manner. A rapid review involves the synthesis of existing knowledge using a simplified systematic review process. Results: A total of sixteen articles were identified for this rapid review. The main findings from these articles included that self-compassion is associated with improved outcomes (psychologically and medically), self-compassion can be improved through interventions, and that many extraneous factors influence levels of self-compassion. Conclusion: It is evident that self-compassion plays a rather significant role in the management of diabetes, and that interventions aimed at developing self-compassion showed success in improving health-related outcomes. It is suggested that future research should build on the possibility of using positive psychology interventions to improve the quality of life of those living with diabetes, and work to better understand the influence of aspects such as gender and diabetes duration on self-compassion.